Effect of Fabricating Parameters on Morphology and Photocatalytic Performance of CdS NCs/TiO2 NTs Photoelectrode for Decomposition of Organic Pollutants1. Issue 11 (27th April 2015) - Cheng, Xiuwen; Pan, Guoping; Yu, Xiujuan
Abstract : CdS NCs/TiO2 NTs photoelectrode was fabricated through anodization, followed by electrodeposition strategy. Meanwhile, some critical parameters were optimized through morphologies observation and photocatalytic decomposition of rhodamine B (RhB). It was found that the optimized deposited potential, deposited time, concentration of cadmium chloride, and concentration of thioacetamide were 0.8 V, 30 min, 0.10 mol L −1, and 0.06 mol L −1, respectively. Under the optimized parameters conditions, the as‐fabricated CdS NCs/TiO2 NTs photoelectrode exhibited superior PC efficiency (72.6%) for the degradation of RhB aqueous solution within 120 min Xenon light irradiation. Furthermore, the effect of fabricating parameters for degradation of RhB aqueous solution fitted well with the pseudo‐first‐order kinetics function. Abstract : A CdS NCs/TiO2 NTs photoelectrode is fabricated through anodization, followed by an electrodeposition strategy. Meanwhile, some critical parameters are optimized through observation of morphologies and photocatalytic decomposition of rhodamine B (RhB). Results show that the influence of fabricating parameters for degradation of RhB aqueous solution fits well with the pseudo‐first‐order kinetics function.